(untitled) (Bangladesh Journal of Medical Education, 2021)
Prescription writing reflects the competency as well as the quality of medical education of the physician. This study was done to evaluate opinion of recent medical graduates towards ethical aspects of prescription writing. This descriptive study was conducted on recent medical graduates of 7 medical colleges in Bangladesh from January’18-June’19. Data were collected by a pretested self administered semi-structured questionnaire. Only descriptive statistics were computed by collected data. The study included 308 recent medical graduates having average age at commencement of internship was 24.2 years with male predominant (53.2%). Majority of the respondents thought that prescription should be written in block letter or be printed (70.1%) and there was possibility for selling wrong medicine due to bad handwriting (77.6%). Majority of the recent medical graduates thought that generic names were not difficult to remember (82.8%), there was every possibility of selling poor quality drugs of the same generic names by the pharmacists (87.7%) and physicians should not use generic name in prescriptions (56.5%). Furthermore, most of them (92%) felt a need for a mandatory educational qualification for the pharmacists. Most participants opined that pharmacists should have a minimum educational qualification to prevent the errors in dispensing. The findings of this study might be helpful to reinforcement the law to avoid the errors related to medical professionalism and ethical aspects of prescription writing in the medical education. Bangladesh Journal of Medical Education Vol.12(1) 2021: 16-21